The impact of democracy on social entrepreneurship - Gura, Viktoriya (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2020)
This article presents a causative approach to the field of connection between social entrepreneurship and democracy. The background of social entrepreneurship appearance and improving of democratic norms in the developed countries are shown. The impact of democracy on social entrepreneurship is described by paying attention on the following issues: (1) Analyzes of different scientists views on the essence of entrepreneurship and entrepreneur. (2) The role of democracy development for forming creative society with free people and freethinking. (3) Situation in the Ukrainian society in the sphere of social entrepreneurship promoting and further strengthen of democratic norms. Introduction of the paper briefly displays the importance of social entrepreneurship increase for society enhancements and growing democratic initiatives. Part I discusses the democratic development and social entrepreneurs activities as main factors for future prosperity of the country. In Part II, the attention is concentrated on social entrepreneurship promoting in Ukraine and its impact for further society development as real example with its peculiarities due to the political and economic situation in the state.